2022
DOI: 10.3389/fpls.2022.884456
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Pennisetum purpureum CCoAOMT Contributes to Lignin Deposition and Drought Tolerance by Promoting the Accumulation of Flavonoids in Transgenic Tobacco

Abstract: Elephant grass (Pennisetum purpureum) is a fast-growing and low-nutrient demand plant that is widely used as a forage grass and potential energy crop in tropical and subtropical regions of Asia, Africa, and the United States. Transgenic tobacco with the PpCCoAOMT gene from Pennisetum purpureum produces high lignin content that is associated with drought tolerance in relation to lower accumulation of reactive oxygen species (ROS), along with higher antioxidant enzyme activities and osmotic adjustment. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…In addition, the first oxidation reaction to generate ρ-coumaric acid in flavonoids synthesis were catalyzed by C4H [55,59]. CCoAOMT and DFR contributed to the accumulation of flavonoids and enhanced plant stress resistance, while GPT2 was necessary for photodynamic domestication [60][61][62]. These findings suggested that 50% shading induced a high expression of enzyme genes, which might increase the content of total flavonoids and total phenolic compounds.…”
Section: Differentiation Of Transcription Levels Under Different Shad...mentioning
confidence: 97%
“…In addition, the first oxidation reaction to generate ρ-coumaric acid in flavonoids synthesis were catalyzed by C4H [55,59]. CCoAOMT and DFR contributed to the accumulation of flavonoids and enhanced plant stress resistance, while GPT2 was necessary for photodynamic domestication [60][61][62]. These findings suggested that 50% shading induced a high expression of enzyme genes, which might increase the content of total flavonoids and total phenolic compounds.…”
Section: Differentiation Of Transcription Levels Under Different Shad...mentioning
confidence: 97%
“…Transgenic Morus alba, expressing the gene encoding cinnamyl-alcohol dehydrogenase (CAD), which catalyzes the final step of monolignol biosynthesis, revealed that the MaCAD family members are responsible for the formation of various monolignols in lignin biosynthesis under drought stress [23]. Overexpression of the Pennisetum purpureum PpCCoAOMT gene promotes lignin accumulation, which is associated with drought tolerance and reduced accumulation of reactive oxygen species [24]. The phytohormones auxin [25,26], cytokinin [27], gibberellin [28,29], brassinosteroids [30], ethylene [31], and abscisic acid [32,33] form a complex regulatory network that controls both vascular cell development during wood formation and plant responses to drought [34].…”
Section: Introductionmentioning
confidence: 99%